Ketidakadilan Gender Novel Azab dan Sengsara Karya Merari Siregar dan Novel Cantik itu Luka Karya Eka Kurniawan - Erizal Gani; Yulia Marizal (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research aims to describe gender injustice in the novel Azab dan Sengsara by Merari Siregar and gender injustice in the novel Cantik itu Luka by Eka Kurniawan. This research uses qualitative research with descriptive methods. Data collection techniques used reading and note-taking techniques. The research data sources are primary data sources, namely (1) the novel Azab dan Sengsara by Merari Siregar (1920), published in Jakarta Balai Pustaka with 163 pages, and (2) the novel Cantik itu Luka by Eka Kurniawan (2002) published in Jakarta PT Gramedia Utama with 505 pages. The results of the data analysis found gender injustice in terms of marginalization, subordination, stereotypes, and violence in the novel Azab dan Sengsara by Merari Siregar and the novel Cantik itu Luka by Eka Kurniawan.